Imperial Germany 1850 - 1918 - Feuchtwanger, E. J. 1924- (Routledge, 2001)
The German empire was founded in triumph in 1871 and crashed in disaster at the end of the First World War. The main themes of Imperial Germany are domestic political developments and their foreign policy context, but it also offers a balanced guide to the economic, social and cultural background of the period. It examines the process of German unification from the aftermath of the 1848 revolutions to its completion with the Franco-Prussian war of 1870. It explores the tensions that arose within an empire formed through war and against the prevailing liberal spirit of the age.The book makes recent debates raised by German scholarship accessible to English-speaking readers and summarizes significant controversies and competing interpretations surrounding imperial German history. This important study analyses questions such as:- How damaging was the discrepancy between political backwardness and economic progress in Imperial Germany?- To what extent was Bismarcks Second Reich the forerunner of Hitlers Third?- How far was the aggressive foreign policy of Wilhelmine Germany the result of domestic tensions?Chronologically structured, this textbook is an ideal source for undergraduates and for those teaching the subject at all levels. It is also indispensable background reading for anyone studying more specific aspects of German history.The AuthorEdgar Feuchtwanger has written widely on modern German history and is the author of Prussia: Myth and Reality (1972) and From Weimar to Hitler: Germany 191833 (2nd edition 1995) and the editor of Upheaval and Continuity: A Century of German History (1973). He has published biographies of Gladstone and Disraeli and taught German and British history at the University of Southampton.